Kajian Eksperimen Pengaruh Sudut Stagger Silinder Di Depan Returning Blade Terhadap Coefficient Of Power Turbin Angin Savonius Sudu Fin Dengan Profile Blade Myring n=1 - Billy Yanuar Saputro; Emie Santoso; Priyo Agus Setiawan (Proceedings Conference on Marine Engineering and its Application, 2023)
Savonius wind turbines are widely used for wind energy utilization eventhough theirperformance is considered lower than other types of turbines. In 3 previous studies, additionaldisturbance cylinder in front of returning blade and additional fin on blade could improve the turbineperformance but the increase was not optimum. Based on these problems, this experimental study usedone additional fin type myring n = 1 on the blade. Circular cylinders have a distance ratio of 340 mm,with various airspeed of 7 m/s, 6 m/s, 5 m/s, and various cylinder angles of 45°, 50°, 55°, 60°. Theexperiment was performed 12 times to determine the effect to coefficient of power (Cp) and coefficientof torque (Ct). The turbine best performance is obtained at a cylinder angle of 60° and a wind speed of6 m/s. The results are 0.394 for coefficient of power (Cp) and 0.688